Manajemen Keuangan Mahasiswa di Era Digital: Dampak Penggunaan E-Wallet terhadap Pola Konsumsi - Cici Widya Prasetyandari (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The digital era is developing rapidly. Technology has made it easier for people to conduct various financial transactions, such as through financial planning applications, mobile banking, e-wallets, and so on. These applications are in demand by various segments of society. Digital wallets, or e-wallets, are a form of technology that facilitates financial transactions. The purpose of this study is to determine the impact of e-wallet use on the consumption behavior of students in the Sharia Financial Management Study Program at Zainul Hasan Islamic University, Genggong, Probolinggo. It is hoped that students will be able to manage their finances effectively in this digital era. This research method is qualitative, with data collection methods including interviews, observation, and documentation. The results show that students use e-wallets for their daily needs. E-wallets can meet students' rational consumption patterns. Students are able to manage their finances well, enabling them to make wise financial decisions.